The Realization of Social Justice For Underprivileged People In Legal Philosophy - Naomi Jesica Hartanto; Meta Nadia; Lusi Septiyati (Legal Spirit, 2018)
ABSTRACT Pancasila is the ideology of Indonesia. One of the precepts of Pancasila is the principle of Social Justice for All Indonesians implies that all Indonesian people have the same position before the law. But nowdays, there have been many cases of injustice against the underprivileged people. Therefore, this research journal is the realization of social justice for the underprivileged people in the philosophy of law, especially based on the theory named Critical Legal Studies. Keywords: Injustice, underprivileged people, Crticial Legal Studies